Entanglement of Cape fur seals (Arctocephalus pusillus pusillus) at colonies in central Namibia. (October 2021) - Curtis, S.; Elwen, S.H.; Dreyer, N.; Gridley, T.
Abstract: Marine pollution is increasing, and pinnipeds are commonly affected by entanglement in waste. We investigated entanglement rates, common materials, and the demographic profile of Cape fur seals ( Arctocephalus pusillus pusillus ) affected at two Namibian colonies. Overall, we identified 366 cases of entanglement, and present a global rate of entanglement of 0.17%. Entanglement rates were 0.17% and 0.15% for the Pelican Point and Cape Cross colonies, respectively. We identified 17% more entanglements through photographs than binocular scans. Of the 347 entanglements analysed in detail, juveniles were most commonly affected and fishing materials were the primary cause of entanglements (53%), with 8% of entangled seals exhibiting 'very severe' injuries. Overall, 191 individuals were successfully disentangled, and citizen scientists contributed 51% of total entanglement data. We highlight the negative impact of plastic marine waste among seals and the importance of disentanglement for individual animal welfare. Highlights: Fishing related materials were the primary cause of seal entanglements in Namibia. Of all age classes, juveniles were most commonly affected by entanglement. Photographs were more reliable than binocular scans in identifying entanglements. Our global entanglement rate for Cape fur seals was 0.17%. Citizen scientists contributed 51% of entanglement data.